2017
DOI: 10.1021/acschemneuro.7b00012
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclic Truncated Analogue of the Marine Toxin Gambierol Modifies NMDA, Tau, and Amyloid β Expression in Mice Brains: Implications in AD Pathology

Abstract: Gambierol and its two, tetra- and heptacyclic, analogues have been previously proved as promising molecules for the modulation of Alzheimer's disease (AD) hallmarks in primary cortical neurons of 3xTg-AD fetuses. In this work, the effect of the tetracyclic analogue of gambierol was tested in vivo in 3xTg-AD mice (10 months old) after 1 month of weekly treatment with 50 μg/kg. Adverse effects were not reported throughout the whole treatment period and no pathological signs were observed for the analyzed organs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The amyloid cascade hypothesis has been the most widely supported explanation of the pathology that drives the progression of AD (De Strooper and Karran, 2016 ; Selkoe and Hardy, 2016 ), although other elements of the neuropathology are gaining increasing attention (Herrup, 2015 ; Rius-Pérez et al, 2015 ; Briggs et al, 2016 ). The amyloid cascade hypothesis contends that there is either a shift in APP processing towards the amyloidogenic pathway, or there is a reduction in Aβ clearance which results in the excessive accumulation of Aβ and a shift in the ratio of the various Aβ species to favor Aβ42.…”
Section: A Shift In the Balance Of α-Secretase Versus β-Secretase Actmentioning
confidence: 99%
“…The amyloid cascade hypothesis has been the most widely supported explanation of the pathology that drives the progression of AD (De Strooper and Karran, 2016 ; Selkoe and Hardy, 2016 ), although other elements of the neuropathology are gaining increasing attention (Herrup, 2015 ; Rius-Pérez et al, 2015 ; Briggs et al, 2016 ). The amyloid cascade hypothesis contends that there is either a shift in APP processing towards the amyloidogenic pathway, or there is a reduction in Aβ clearance which results in the excessive accumulation of Aβ and a shift in the ratio of the various Aβ species to favor Aβ42.…”
Section: A Shift In the Balance Of α-Secretase Versus β-Secretase Actmentioning
confidence: 99%
“…Interesting results were obtained using a tetracyclic analogue of ciguatoxin-like toxin, gambierol, in cellular and animal models for AD. In fact, although gambierol exhibits a potent acute lethal toxicity in mice (minimal lethal dose: 50 µg/kg, ip), its tetracyclic truncated analogue in a mouse model for AD induces a decrease of amyloid β1−42 level, a reduction of tau phosphorylation, and a reduction in the N2A subunit of the N-methyl-Daspartate (NMDA) receptor level [92].…”
Section: Ciguatoxinsmentioning
confidence: 99%
“…They have found that 170 – 172 decreased both intra- and extracellular Aβ levels and tau hyperphosphorylation via modulation of N -methyl-D-aspartate (NMDA) receptors that is possibly secondary to voltage-gated potassium (K v ) channel inhibition in an in vitro mouse model of AD [ 95 ]. Furthermore, both 170 and 172 displayed a dose-dependent inhibition of BACE-1 activity, falling to 52.25% with 170 and to 58.04% with 172 , at 10 µM [ 96 ].…”
Section: Marine-derived Compounds That Inhibit β-Secretase (Bace-1) and γ-Secretase Activitiesmentioning
confidence: 99%